Faktor-faktor yang Berhubungan dengan Persiapan Persalinan pada Ibu Hamil di Kelurahan Anduring - Novria Hesti; Zulfita Zulfita; Refki Ryantori (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The unpreparedness of the mother in facing childbirth is one of the factors causing the Maternal Mortality Rate (MMR). For this reason, efforts to reduce MMR are carried out, preparation for childbirth is an important thing that must be improved. Preparation for childbirth can be done with various preparations ranging from increasing maternal knowledge, preparing costs, blood donation, choosing a place of delivery and birth attendants as well as preparing companions. In addition, through classes for pregnant women, preparation for childbirth can also be carried out, where with Antenatal Care visits according to standards, pregnant women can get information about the structure of pregnancy care, childbirth, postpartum, and newborn care. The purpose of this study was to determine the relationship between age, education level, family income, family support and prenatal care with preparation for delivery of pregnant women in Anduring Village. This type of research is analytic with a cross sectional study design. The study was carried out in the Anduring village of Padang city in July-November 2021. Sampling was carried out using the Total Sampling technique, where the total sample was all pregnant women who met the inclusion criteria. The sample of this study was pregnant women in the second-third trimester in Anduring village, amounting to 32 people. Data were collected using a questionnaire and analyzed by univariate and bivariate with chi-square test. There is a significant relationship between the level of education, family income, prenatal care and family support with preparation for delivery in pregnant women and there is no significant relationship between the age and occupation of the mother with labor preparation. It is hoped that midwives will optimize the use of the MCH handbook during Antenatal Care visits as a form of information and support for pregnant women, activate classes for pregnant women and involve their husbands in the activities of the pregnant classes, and provide counseling for preparation for delivery to pregnant women.